2021
DOI: 10.1371/journal.pone.0260731
|View full text |Cite
|
Sign up to set email alerts
|

Time trends, factors associated with, and reasons for COVID-19 vaccine hesitancy: A massive online survey of US adults from January-May 2021

Abstract: Importance COVID-19 vaccine hesitancy has become a leading barrier to increasing the US vaccination rate. Objective To evaluate time trends in COVID-19 vaccine intent during the US vaccine rollout, and identify key factors related to and self-reported reasons for COVID-19 vaccine hesitancy in May 2021. Design, participants and setting A COVID-19 survey was offered to US adult Facebook users in several languages yielding 5,088,772 qualifying responses from January 6 to May 31, 2021. Data was aggregated by m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
75
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 20 publications
13
75
1
1
Order By: Relevance
“…A recent study in the US showed a similar pattern with those with lower levels of education showing less hesitancy than those with higher. [49] This is contrary to the results obtained in other studies. [35-37,42-43] A statement by a 61 year old on Africa news may provide an insight into the mindset of those who are less educated thereby making them more likely to accept vaccination: “If in the time of our mothers, in the time we were little children if these “WhatsApp doctors” had existed (people who post unreliable medical information on social media) I think we would have all died because our mothers who did not go to school agreed to vaccinate us against smallpox, measles, polio -- all the other diseases without debate.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…A recent study in the US showed a similar pattern with those with lower levels of education showing less hesitancy than those with higher. [49] This is contrary to the results obtained in other studies. [35-37,42-43] A statement by a 61 year old on Africa news may provide an insight into the mindset of those who are less educated thereby making them more likely to accept vaccination: “If in the time of our mothers, in the time we were little children if these “WhatsApp doctors” had existed (people who post unreliable medical information on social media) I think we would have all died because our mothers who did not go to school agreed to vaccinate us against smallpox, measles, polio -- all the other diseases without debate.…”
Section: Discussioncontrasting
confidence: 74%
“…Local East African respondents were three times more likely to resist and almost five times more likely to be hesitant than West Africans. This may be due to misinformation about COVID-19 [48] and its vaccines [49] which was reported to be more common in East African countries such as Tanzania. The results showed that the least educated respondents were less likely to be resistant or hesitant.…”
Section: Discussionmentioning
confidence: 99%
“…population studies that examined COVID-19 vaccine uptake by demographic association (15,16), our study demonstrates that participants who routinely get flu vaccinations and are older in age were the most likely groups to get vaccinated against COVID-19. This is also in agreement with state-wide data from the PA Department of Health, showing highest vaccination rates among older citizens (>99% vaccinated in 65+ age groups).…”
Section: Discussionmentioning
confidence: 69%
“…While this may be due to our sample size, an important confounder to consider is the health literacy of the Turtle Creek community. Groups most likely to not pursue vaccination are also less likely to be concerned about themselves or family members contracting COVID-19 (1), more likely to believe the virus was manufactured or pandemic exaggerated, hold Republican political beliefs (4,16,17), and have decreased health literacy as demonstrated by knowing less about the safety and science of COVID-19 vaccines (14).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine hesitancy, or the belief in conspiracy theories related to COVID-19 and misinformation about the COVID-19 pandemic and vaccines on social media have been important factors that impede COVID-19 preventive efforts, including timely vaccination coverage [64,65]. Other reasons for COVID-19 vaccine hesitancy include individuals' concerns about the adverse effects of COVID-19 vaccines, lack of trust in COVID-19 vaccines, planning to wait and see if the vaccines are safe, believing that COVID-19 is not a serious disease, believing that there is no need for the vaccines or being not sure about their effectiveness [66,67]. Therefore, it is important for governments to work on educating the population against these conspiracy theories, as such theories could jeopardize the strategies to mitigate the spread of COVID-19 and prevent timely and wide vaccination coverage of the populations [64,68,69].…”
Section: Introductionmentioning
confidence: 99%